Digitalisasi Manajemen Pendidikan Islam dan Ekonomi Syariah di Perguruan Tinggi - Maadi, Alan Suud (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2018)
Management of Islamic education and Sharia Economics has experienced rapid development and progress. The digital era brings significant changes to both dimensions of science in various aspects of life. In addition, Islamic Education Management and Sharia Economics is a national subsystem in direct contact with the pattern of community life. So it is necessary to get around and find solutions by looking at the various opportunities and challenges in printing golden generation is multidimensional. This paper will describe the strategies, opportunities and challenges of Islamic education management and Islamic economics in universities in the digital era with a library research approach. Furthermore, in this paper will also describe the condition of the global level to provide an overview of the Indonesian context. the results of this study that the opportunities and challenges of universities in internal and external aspects. The strategy by improving the scientific culture of digital learning trends and virtual based services.